1982
DOI: 10.2337/diab.31.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Phagocytic Function and Increased Immune Complexes in Diabetics with Severe Microangiopathy

Abstract: An increase in circulating immune complexes (AgAb) of medium size has been observed in diabetics with late complications. This increase may be related either to an increased formation or reduced clearance. Alternatively, both mechanisms may be involved. As medium-sized AgAb determined by the C1q solid phase method are mainly removed from circulation by the fixed phagocytes of the reticulo-endothelial system, we investigated the function of these cells using a colloid clearance test in diabetics with various de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Impairment of the immune system in diabetic subjects is well defined, and its relevance to alteration of phagocytic properties of monocytes/macrophages has also been proposed (22)(23)(24). In the present study, we investigated the involvement of AGE formation in the reduction of phagocytic activity of diabetic macrophages by using flow cytometric analysis with fluorescence-labeled latex particles.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Impairment of the immune system in diabetic subjects is well defined, and its relevance to alteration of phagocytic properties of monocytes/macrophages has also been proposed (22)(23)(24). In the present study, we investigated the involvement of AGE formation in the reduction of phagocytic activity of diabetic macrophages by using flow cytometric analysis with fluorescence-labeled latex particles.…”
Section: Discussionmentioning
confidence: 96%
“…These results suggest the involvement of advanced stages of the Maillard reaction after addition of Amadori product in the phagocytic activity of macrophages. Iavicoli et al (24) reported that the colloid clearance was signific a n t l y reduced in diabetes associated with severe microangiopathy, compared with patients who had no sign of microangiopathy or with normal subjects. They suggested that increased circulating immune complexes in patients with severe microangiopathy may result from an impaired function of fix e d phagocytes.…”
Section: Downregulation Of Phagocytosis Byagesmentioning
confidence: 98%
See 1 more Smart Citation